2022
DOI: 10.3390/ijms23020589
|View full text |Cite
|
Sign up to set email alerts
|

G9a Knockdown Suppresses Cancer Aggressiveness by Facilitating Smad Protein Phosphorylation through Increasing BMP5 Expression in Luminal A Type Breast Cancer

Abstract: Epigenetic abnormalities affect tumor progression, as well as gene expression and function. Among the diverse epigenetic modulators, the histone methyltransferase G9a has been focused on due to its role in accelerating tumorigenesis and metastasis. Although epigenetic dysregulation is closely related to tumor progression, reports regarding the relationship between G9a and its possible downstream factors regulating breast tumor growth are scarce. Therefore, we aimed to verify the role of G9a and its presumable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In the heterochromatin, such as the pericentromeric regions, SUV39H1 can catalyze H3K9me2, while SUV39H2 catalyzes H3K9me3 ( Rea et al, 2000 ). G9a plays a critical part in BC occurrence ( Jin et al, 2022 ) as shown in Figure 2 . Its activation can suppress anticancer genes, thereby promoting BC cell growth and migration.…”
Section: Histone Modifications Within Bcmentioning
confidence: 99%
“…In the heterochromatin, such as the pericentromeric regions, SUV39H1 can catalyze H3K9me2, while SUV39H2 catalyzes H3K9me3 ( Rea et al, 2000 ). G9a plays a critical part in BC occurrence ( Jin et al, 2022 ) as shown in Figure 2 . Its activation can suppress anticancer genes, thereby promoting BC cell growth and migration.…”
Section: Histone Modifications Within Bcmentioning
confidence: 99%
“…The levels of G9a were also significantly higher in metastatic samples than in primary tumor samples, and this was associated with complex formation with lysine acetyltransferase 2B (P300) and the glucocorticoid receptor (GR), resulting in the increased expression of integrin subunit beta 3 (ITGB3) and promoting peritoneal metastasis [ 29 ]. The increased expression of G9a in breast cancer and head and neck squamous cell carcinoma was also shown to repress E-cadherin, thus promoting metastasis [ 30 , 31 ]. In endometrial cancer, the upregulation of G9a was associated with myometrial invasion through the silencing of E-cadherin [ 32 ].…”
Section: Ehmt1/glp and Ehmt2/g9a Dysregulation In Cancermentioning
confidence: 99%
“…20 G9a plays a significant role in the formation of heterochromatin, DNA methylation, 21 transcriptional silencing, 22 proliferation, apoptosis, differentiation, and movement of tumor cells. 23 Knockdown of G9a significantly reduced the di-and trimethylation of H3K9 in cells and in mice, increased the sensitivity of cells to radiation treatment, and sensitized cells to DNA damage agents. 24 progress in the development of substrate-competitive G9a inhibitors, none has entered the clinical phase until now.…”
Section: ■ Introductionmentioning
confidence: 97%
“…G9a [also known as KMT1C (lysine methyltransferase 1C) or EHMT2 (euchromatic histone methyltransferase 2)] is a histone-lysine N -methyltransferase with S -adenosylmethionine (SAM) as a methyl donor that catalyzes the transfer of one or two methyl groups to the ε-amino group of lysine 9 of histone H3 (H3K9me1 and H3K9me2), , a hallmark associated with transcriptional gene silencing . G9a plays a significant role in the formation of heterochromatin, DNA methylation, transcriptional silencing, proliferation, apoptosis, differentiation, and movement of tumor cells . Knockdown of G9a significantly reduced the di- and trimethylation of H3K9 in cells and in mice, increased the sensitivity of cells to radiation treatment, and sensitized cells to DNA damage agents .…”
Section: Introductionmentioning
confidence: 99%